2018
DOI: 10.5713/ajas.18.0481
|View full text |Cite
|
Sign up to set email alerts
|

Potential to mitigate ammonia emission from slurry by increasing dietary fermentable fiber through inclusion of tropical byproducts in practical diets for growing pigs

Abstract: Modest dietary inclusion of tropical byproducts to increase fermentable fiber might stimulate faecal VFA excretion but this does not guarantee a reduction in ammonia emissions from slurry, while its interaction with protein digestibility even might increase the risk of enhanced ammonia emissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previous studies have explored the increased VFA content in pig slurry resulting from fibrous feedstuffs [47,48]. However, even though the peat moss used in our study had a high fiber content, a 3% inclusion of peat moss had a limited impact on enhancing VFA levels in the pig slurry.…”
Section: Concentration Of Volatile Fatty Acid (Vfa) In Pig Slurrymentioning
confidence: 79%
“…Previous studies have explored the increased VFA content in pig slurry resulting from fibrous feedstuffs [47,48]. However, even though the peat moss used in our study had a high fiber content, a 3% inclusion of peat moss had a limited impact on enhancing VFA levels in the pig slurry.…”
Section: Concentration Of Volatile Fatty Acid (Vfa) In Pig Slurrymentioning
confidence: 79%
“…The correlation analysis results in this study showed that both NH 3 and H 2 S were positively correlated with total VFAs (r = 0.771, p < 0.1). Undigested protein fermentation in the caecum is a major source of odours, and the fermentation of these kinds of protein may produce potentially odorous end products, including indoles, NH 3 , H 2 S and branched-chain fatty acids [ 41 ]. Additionally, protein fermentation is often reported to be accompanied by carbohydrate fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…The fibre components of NDF, ADF and Lignin were analysed on the Ankom system (A200). Ammonia in silage was analyzed using the technique described by Chaney and Marbach (1962) and a detailed processing was described by Nguyen et al (2019).…”
Section: Chemical Analysismentioning
confidence: 99%